Saline water, nitrogen and phosphorus on water relations and physiological aspects of West Indian cherry - Sá, Francisco Vanies da Silva; Gheyi, Hans Raj; Lima, Geovani Soares de; Paiva, Emanoela Pereira de; Lacerda, Claudivan Feitosa; Fernandes, Pedro Dantas (Comunicata Scientiae, 2018)
Salinity is a common problem in arid and semi-arid regions, causing great damage to crop yields, and management strategies that reduce the effects of salt stress on plants are necessary. So, the aim of this study was to evaluate the interaction between salinity, nitrogen and phosphorus on water relations, gas exchange and chloroplastidic pigments of the West Indian cherry in the vegetative/reproductive phase transition. The cultivation was carried out in a greenhouse, in lysimeters filled with an Entisol of low phosphorus content. The experiment was arranged in a randomized complete block design, arranged in a factorial scheme with two factors, being five levels of electrical conductivity of irrigation water (ECw)(0.6, 1.4, 2.2, 3.0 and 3.8 dS m-1) and four P:N rates (100:100, 140:100, 100:140 and 140:140% of recommendation) with three replications and one plant per plot. The analysis of results indicated that the seedlings of West Indian cherry cultivar BRS 366-Jaburu, grafted on the Criolo rootstock from the EMBRAPA Agroindústria Tropical in Pacajus-CE were used. Irrigation with saline water of up to 3.8 dS m-1 does not affect the water status of the West Indian cherry. Increased salinity of irrigation water reduces gaseous exchange activity and increases the percentage of leaf cell damage in the West Indian cherry. The 40% increase over recommended level in nitrogen supply increases the synthesis of chlorophyll b and carotenoids in the West Indian cherry, when irrigated with saline water of up to 2.2 dS m-1.